2022
DOI: 10.1001/jama.2022.18931
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Global Proportions of Individuals With Persistent Fatigue, Cognitive, and Respiratory Symptom Clusters Following Symptomatic COVID-19 in 2020 and 2021

Abstract: ImportanceSome individuals experience persistent symptoms after initial symptomatic SARS-CoV-2 infection (often referred to as Long COVID).ObjectiveTo estimate the proportion of males and females with COVID-19, younger or older than 20 years of age, who had Long COVID symptoms in 2020 and 2021 and their Long COVID symptom duration.Design, Setting, and ParticipantsBayesian meta-regression and pooling of 54 studies and 2 medical record databases with data for 1.2 million individuals (from 22 countries) who had s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
324
2
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 559 publications
(453 citation statements)
references
References 92 publications
20
324
2
8
Order By: Relevance
“…Future studies should examine the effects of long-COVID-19 on attitudes in greater depth. The literature on COVID-19 and vaccine hesitancy research does not broadly address long-COVID-19 [ 33 , 34 , 35 , 36 , 37 ]. However, studies on people who have experienced COVID-19 or who have been exposed to the experiences of people close to them revealed that there is a significant relationship between vaccine hesitancy and these experiences [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should examine the effects of long-COVID-19 on attitudes in greater depth. The literature on COVID-19 and vaccine hesitancy research does not broadly address long-COVID-19 [ 33 , 34 , 35 , 36 , 37 ]. However, studies on people who have experienced COVID-19 or who have been exposed to the experiences of people close to them revealed that there is a significant relationship between vaccine hesitancy and these experiences [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-COVID-19 is a definition used to describe the disease in people who have recovered from the COVID-19 disease but still report lasting effects of the infection or have usual symptoms for much longer than expected [ 32 ]. Lately, there are a growing number of studies on long-COVID, whose symptoms can occur in many different ways [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“… 123 The persistent existence of SARS‐CoV‐2 antigens such as the receptor binding domain (RBD) of Spike, RdRp, and nucleocapsid antigen (not infectious virus) enables a continuously activated and robust immune response, which contributes to the development of long COVID. 109 , 200 Recently, researches found alterations in genes express in olfactory epithelium and involve in the metabolism of odor molecules, indicating a new mechanism of long COVID smell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…affects anywhere from less than 10% to between 20% and 40% of people after acute infection; up to 50%-70% of patients because of COVID-19 may continue to have symptoms months following hospital discharge. [10][11][12][13][14][15] Patients with SARDs may be vulnerable to PASC due to altered immunity, immunosuppressive therapy, and increased risk for severe acute COVID-19.…”
Section: Epidemiologymentioning
confidence: 99%